INVESTIGATION OF BIOACTIVITIES FROM CASSIA FISTULA LINN. EXTRACTS - Sriwatcharakul, S. (My University, 2025)
This study explores the bioactivities of Cassia fistula Linn. (commonly known as the golden shower tree) by comparing the antioxidant, antibacterial, and cytotoxic properties of pod and seed ethanol extracts collected from Chonburi and Samut Prakan provinces in Thailand. The antioxidant potential was assessed through DPPH radical scavenging assay, where pod extracts exhibited higher activity than seed extracts, with IC₅₀ values of 0.98 and 1.09 mg/ml, respectively. The total phenolic content was highest in seed extracts from Samut Prakan (205.00 mg GAE/g extract), followed closely by pod extracts from Chonburi (167.50 mg GAE/g extract). Antibacterial screening via agar disc diffusion method showed that all extracts had significant inhibitory activity against gram positive; Bacillus subtilis and Micrococcus luteus. Samut Prakan pod extract inhibit M. luteus better than gentamicin. Cytotoxicity tests against MCF-7 breast carcinoma cells indicated that all extracts were non-toxic, and some even promoted cell viability, suggesting safety for potential therapeutic applications. These findings suggest that Cassia fistula, particularly its pod extracts, is a promising natural source candidate for future development in health-related applications.
Keywords: Antibacterial; Antioxidant; Cassia fistula; Cytotoxic; MCF-7